Learning potential measurement with Spanish-speaking IQ test: A first report - Budoff, Milton; Louise Corman, Alex Gimon (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The learning potential (LP) procedure represents an alternative method of measuring the general ability of Spanish-speaking students who tend to score low on traditional IQ tests. The relative predictive power of LP and IQ measures on achievement scores was compared for Spanish-speaking students. Subjects were administered the Raven and Series LP procedures, the WISC Performance Scale in Spanish, the WISC vocabulary subtest, Picture Motivator Scale, and an achievement test in Spanish and English, Numeric and nonverbal achievement in both Spanish and English were significantly related to post-training Series LP scores, WISC performance IQ, and age. WISC vocabulary scores were related only to verbal achievement in the same language. The LP procedure resulted in increased levels of performance on a reasoning task and predicted achievement better than verbal IQ for these students.